Rotational effect of buoyancy in frontcrawl: does it really cause the legs to sink? - Yanai, T. (Journal of Biomechanics, 2001)
The purposes of this study were to quantify the rotational effect of buoyant force (buoyant torque) during the performance of front crawl and to reexamine the mechanics of horizontal alignment of the swimmers. Three-dimensional videography was used to measure the position and orientation of the body segments of 11 competitive swimmers performing front crawl stroke at a sub-maximum sprinting speed. The dimensions of each body segment were defined mathematically to match the body segment parameters (mass, density, and centroid position) reported in the literature. The buoyant force and torque were computed for every video-field (60 fields/s), assuming that the water surface followed a sine curve along the length of the swimmer. The average buoyant torque over the stroke cycle (mean=22 N m) was directed to raise the legs and lower the head, primarily because the recovery arm and a part of the head were lifted out of the water and the center of buoyancy shifted toward the feet. This finding contradicts the prevailing speculation that buoyancy only causes the legs to sink throughout the stroke cycle. On the basis of a theoretical analysis of the results, it is postulated that the buoyant torque, and perhaps the forces generated by kicks, function to counteract the torque generated by the hydrodynamic forces acting on the hands, so as to maintain the horizontal alignment of the body in front crawl.